Validation of a novel molecular diagnostic panel for pediatric musculoskeletal infections: Integration of the Cepheid Xpert MRSA/SA SSTI and laboratory-developed real-time PCR assays for clindamycin resistance genes and Kingella kingae detection - Searns, Justin B.; Robinson, Christine C.; Wei, Qi; Yuan, Ji; Hamilton, Stacey; Pretty, Kristin; Donaldson, Nathan; Parker, Sarah K.; Dominguez, Samuel R. (Journal of microbiological methods, 2019)
Pathogen detection in pediatric patients with musculoskeletal infections relies on conventional bacterial culture, which is slow and can delay antimicrobial optimization. The ability to rapidly identify causative agents and antimicrobial resistance genes in these infections may improve clinical care. Convenience specimens from bone and joint samples submitted for culture to Children's Hospital Colorado (CHCO) from June 2012 to October 2016 were evaluated using a “Musculoskeletal Diagnostic Panel” (MDP) consisting of the Xpert MRSA/SA SSTI real-time PCR (qPCR, Cepheid) and laboratory-developed qPCRs for Kingella kingae detection and erm genes A, B, and C which confer clindamycin resistance. Results from the MDP were compared to culture and antimicrobial susceptibility testing (AST) results. A total of 184 source specimens from 125 patients were tested. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the Xpert MRSA/SA SSTI compared to culture and AST results were 85%, 98%, 93%, and 95% respectively for MSSA and 82%, 100%, 100%, and 99% for MRSA. Compared to phenotypic clindamycin resistance in S. aureus isolates, the erm A, B, and C gene PCRs collectively demonstrated a sensitivity, specificity, PPV, and NPV of 80%, 96%, 67%, and 98%. In comparison to clinical truth, Kingella PCR had a sensitivity, specificity, PPV, and NPV of 100%, 99.5%, 100%, and 100%. This novel MDP offers a rapid, sensitive, and specific option for pathogen detection in pediatric patients with musculoskeletal infections.